APLIKASI PERHITUNGAN IP ADDRESS DENGAN METODE SUBNETTING BERBASIS ANDROID - Setiawan, Ade; Darma Astuti, Rachmawati; Mustofa, Mustofa; Dessy Susanti, Inggit (Aksara Public, 2019)
Calculating IP address subentting can be difficult if the CIDR value has a large number of subnets. An example of a class A IP address has a CIDR / 17 value, so if we calculate it manually and create a table there will be thousands of tables that we cannot count one by one to get the IP subnet, initial IP, final IP and IP broadcast. Many technicians working in network computer engineering are confused in calculating IP addresses if the value of the subnet is large. Therefore the author makes the application of the IP address subnetting calculation to make it easier for network technicians, students and students. Of course this application is based on Android because Android users are also getting more and more. In making the application the writer uses indigo java based eclipse tools and design planning using UML (Unified Modeling Language)